Anxiety and depressive symptomatology among children and adolescents exposed to the COVID-19 pandemic – A systematic review - Djurdjević, Sanja; Conde Ghigliazza, Ileana; Dukanac, Vesna; Djurdjević, Ana (Vojnosanitetski pregled, 2022)
Background/Aim. Children and adolescents are sensitive groups for the development of mental disorders during the crisis. The aim of this systematic review was to assess the impact of the COVID-19 pandemic on anxiety and depressive symptomatology in the population of children and adolescents. Methods. The investigation was based on a systematic review followed by PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, including Ovid MEDLINE, Embase, Global Health, and APA Psyc Info databases, to identify relevant studies reporting anxiety and depressive symptoms among children and adolescents during the COVID-19 pandemic. A total of 27 articles were included. Results. Anxiety symptoms increased from 28.3% before the pandemic to 49.5% during confinement [General Anxiety Disorder (GAD)-7 ≥ 11)] (McNemar test, p < 0.0001). More depressive symptomatology was found, as well as weight and sleep disturbances which are the characteristics of children and adolescents’ mental health. Additionally, female teenagers were experiencing grater declines in mood disorders than male teenagers during the COVID-19 crisis. On the one hand, different positive correlations between anxiety and other variables, were found, such as clinical depressive symptoms and anxiety (3/14), smartphone and internet addiction (2/14), lower levels of family income (2/14), perceived threats (2/14), higher grades at school (2/14), and loneliness (1/14). On the other hand, positive correlations were reported between depression and children and adolescents that were socially disconnected (3/17). Finally, mothers with higher level of education and income were associated with higher level of happiness (2/17). Conclusion. COVID-19 has a strong impact on the mental health of children and adolescents regarding depression and anxiety symptoms. Prevention programs focused on coping strategies should be conducted in elementary schools, middle schools, and high schools. Mental health should become a priority matter for governments, and the current pandemic could be an opportunity to highlight the importance of mental well-being and to invest in the betterment of clinical trainings, treatments and mental health research.